Strategic Steps in Dealing with Indonesia's Foreign Debt Through a Political-Economic Perspective - Moh Azfahani Zain; Bilal Kautsar Setiabudi; Kholilur Rohman; Mashudi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This research analyzes the strategic steps that Indonesia can take in facing foreign debt challenges from a political-economic perspective. Indonesia's foreign debt has become an important issue in recent decades, with its impact not only on economic stability, but also in the domestic and international political context. Using a political economy theory approach, this research seeks to explain the interaction between economic policy, political interests and global dynamics in debt management. This research finds that an effective debt management strategy requires a combination of disciplined fiscal policy, strong economic diplomacy, and diversification of financing sources. Through these steps, Indonesia can minimize the risk of dependence on foreign debt and increase economic independence.